Glutinous rice varietal screening for "royal bibingka" (native rice cake) (2002)
Five glutinous rice varieties, namely: IR 65, IMS 2, IMS 5, MS 6 and BPI Ri-1 were evaluated as basic material for "Royal Bibingka" using the formulation, baking procedure and topping found to be desirable by Ilocano consumers in 1991 and improved in 1997 by S.N. de la Cruz of MMSU, Batac, Ilocos Norte. The standard cooking time of 15 minutes steaming to gelatinize the batter mixture and another 15 minutes in the oven to attain the desired color of the product was used in the study. Of the six trials made in six groups of tasters (students, male faculty, female faculty, administrative staff, IRRI-UPLB-PhilRice researchers and a selected trained taste panel as the experts), IR 65 was found to be the 0best in a 9-point scale Hedonic test. It is only this variety where tasters in all categories made a rating of "like extremely". All of the other varieties had the highest rating in the category "like very much". The least desired among the four varieties was BPI Ri 1 although it was still rated as "like slightly" by the panel of evaluators. The other desirable characteristics of IR 65 as a basic material for "Royal bibingka" are its high yielding capacity, good flavor, fine texture, golden brown color of the baked "bibingka" and stable shape of the product. The problems with the IMS lines are production of bibingka that are too sticky, seems to be watery and a shape is hard to maintain. As to BPI Ri 1, the texture seems to be tough and coarse under the formulation and cooking time used in the study.
Keywords: Rice varieties; Rice cakes